Adaptivity in Crashworthiness Calculations - Ted Belytschko; Sang-Ho Lee; I-Sheng Yeh; Jerry I. Lin; Chen-Shyh Tsay; James M. Kennedy (Shock and Vibration)
h-Adaptive finite element methods for nonlinear transient analysis by explicit time integration are described. Examples are given of adaptive calculations for simple components and prototype calculations for a full car model. h-Adaptivity offers substantial reductions in data preparation costs and improvements in accuracy.